Cardiac involvement in post-SARS-CoV-2 multisystem inflammatory syndrome in children (Archives of Pediatrics of Uruguay, 2023)
Objective: describe the characteristics of 8 children who presented Multisystem Inflammatory Syndrome associated with SARS-CoV2 infections (MIS-C) and cardiac involvement.Material and methods: descriptive, retrospective study of 8 patients of between 1 and 13 years of age, diagnosed with MIS-C and cardiac involvement, assisted at the Pereira Rossell Children Hospital, analysis of their medical records, evolution and treatment.Results: the patients showed: fever in 100% of the cases, rash and conjunctival hyperemia in 88%, digestive symptoms in 50%, respiratory failure in 25% and shock in 50%. All required admission to Intensive Care. Cardiac contractility alteration was present in 63% of patients, the affectation was mild and segmental in 80%, 60% required inotropic support for 3 days and recovered normal functions in 7 days.Mitral regurgitation was present in 25% of the cases and pericardial effusion in 38%, mild in both cases. One patient had dilated coronary arteries with a Z score
Keywords: Systemic inflammatory response syndrome; COVID-19; SARS-CoV-2; Heart disease